Penerapan Terapi Bermain Mewarnai Gambar Terhadap Tingkat Kecemasan Hospitalisasi Pada Anak Prasekolah di Ruang Flamboyan 9 RSUD dr. Moewardi - Nanda Putri Larasati; Anjar Nurrohmah; Suciana Ratrinaningsih (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: In sick children, their interests and activities will change, especially if the child needs to be hospitalized. Hospitalization is a child's experience while undergoing treatment in hospital. Prevalence of hospital anxiety in RSUD Dr. Moewardi , the number of children treated in the preschool age ward, namely the flamboyan ward, during the last 4 months starting from January to March 2024 was 465 patients, with 286 preschool age patients and anxiety nursing problems as many as 226 patients. One way to overcome hospital anxiety is play therapy. Objective: to determine the results of anxiety values when applying coloring play therapy in Flamboyan Room 9 Dr Moewardi Hospital. Method: This type of research is a case study that describes anxiety before and after coloring picture play therapy. Results: The results of the application to 2 respondents which were carried out for 2 days with a frequency of 30 minutes a day showed that there was a therapeutic effect of playing coloring pictures. Conclusion; There were differences in the results of anxiety scores before and after the coloring picture play therapy intervention.